Anaerobic lipopeptide biosurfactant production by an engineered bacterial strain for in situ microbial enhanced oil recovery. Issue 33 (10th April 2017) - Liang, Xiaolong; Shi, Rongjiu; Radosevich, Mark; Zhao, Feng; Zhang, Yingyue; Han, Siqin; Zhang, Ying
Abstract : Anaerobic lipopeptide biosurfactant production by engineered bacterial strain FA-2 was fulfilled for in situ MEOR potential application. Abstract : Bacillus mojavensis JF-2 produces water-soluble lipopeptide under aerobic conditions, while Pseudomonas stutzeri DQ1 grows rapidly under anaerobic conditions. These bacteria were used to construct an engineered strain for anaerobic lipopeptide production by protoplast fusion for potential use in microbially enhanced oil recovery (MEOR). The resulting fusant strain FA-2 produced lipopeptide (382 mg l −1 ) anaerobically at temperatures up to 50 °C, across a pH range of 4.5–10.0, and at salt concentrations as high as 10% NaCl. Experimental results from a physical simulation core at 39 °C suggest that FA-2 has potential for use in MEOR.